2021
DOI: 10.3389/fnins.2021.701919
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Vicarious Social Defeat Stress and Western-Style Diets During Adolescence Leads to Physiological Dysregulation, Decreases in Reward Sensitivity, and Reduced Antidepressant Efficacy in Adulthood

Abstract: A dramatic increase in the prevalence of major depression and diet-related disorders in adolescents has been observed over several decades, yet the mechanisms underlying this comorbidity have only recently begun to be elucidated. Exposure to western-style diet (WSD), high in both fats (45% kcal) and carbohydrates (35% kcal): e.g., high fat diet (HFD), has been linked to the development of metabolic syndrome-like symptoms and behavioral dysregulation in rodents, as similarly observed in the human condition. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Studies using this approach have yielded findings that are generally consistent with the human literature with repeated social defeat producing increased “depressive-like” symptoms in both mice and rats ( Iñiguez et al, 2016 ; Burke et al, 2017 ; Alves-Dos-Santos et al, 2020 ; Shimizu et al, 2020 ; Mancha-Gutiérrez et al, 2021 ). These behavioral effects also emerge under circumstances where adolescent mice witness, but are not directly involved in, social defeat, a paradigm called vicarious social defeat (VSD) ( Finnell et al, 2018 ; Garcia-Carachure et al, 2020 ; Warren et al, 2020 ) and can be further exacerbated by additional environmental adversities, such as eating an unhealthy diet ( Sial et al, 2021 ). Although the majority of studies using chronic social defeat in adolescence have examined males, due to the ease with which aggressive mice and rats will attack smaller males, studies using the VSD procedure in adolescent male and female rodents have shown roughly similar effects across sexes ( Finnell et al, 2018 ; Warren et al, 2020 ), Social defeat studies have identified changes in the same brain regions shown to be altered after the LBN approach, including the hippocampus, prefrontal cortex, ventral tegmental area and nucleus accumbens ( Rodríguez-Arias et al, 2018 ; Blanco-Gandia et al, 2019 ).…”
Section: Mixed and Multiple Hit Modelsmentioning
confidence: 99%
“…Studies using this approach have yielded findings that are generally consistent with the human literature with repeated social defeat producing increased “depressive-like” symptoms in both mice and rats ( Iñiguez et al, 2016 ; Burke et al, 2017 ; Alves-Dos-Santos et al, 2020 ; Shimizu et al, 2020 ; Mancha-Gutiérrez et al, 2021 ). These behavioral effects also emerge under circumstances where adolescent mice witness, but are not directly involved in, social defeat, a paradigm called vicarious social defeat (VSD) ( Finnell et al, 2018 ; Garcia-Carachure et al, 2020 ; Warren et al, 2020 ) and can be further exacerbated by additional environmental adversities, such as eating an unhealthy diet ( Sial et al, 2021 ). Although the majority of studies using chronic social defeat in adolescence have examined males, due to the ease with which aggressive mice and rats will attack smaller males, studies using the VSD procedure in adolescent male and female rodents have shown roughly similar effects across sexes ( Finnell et al, 2018 ; Warren et al, 2020 ), Social defeat studies have identified changes in the same brain regions shown to be altered after the LBN approach, including the hippocampus, prefrontal cortex, ventral tegmental area and nucleus accumbens ( Rodríguez-Arias et al, 2018 ; Blanco-Gandia et al, 2019 ).…”
Section: Mixed and Multiple Hit Modelsmentioning
confidence: 99%
“…The majority of work investigating CSDS has shown that repeated exposures to social defeat stress in mice causes a robust depression-like phenotype marked by increased social withdrawal, increased immobility in the forced swim test, reduced sucrose preference (a measure of anhedonia), physiological dysregulation, and decreases in reward sensitivity (Golden et al, 2011 ; Iñiguez et al, 2014 ; Sial et al, 2021 ). Much of this work has been extremely beneficial to understanding how early experiences can predispose animals to cope with stressful events experienced in later life.…”
Section: Introductionmentioning
confidence: 99%
“…[152]. In another study, HFD-fed mice subjected to a vicarious social defeat stress, wherein one mouse witnesses the physical defeat of a conspecific from the safety of an adjacent compartment (i.e., uncoupling of emotional and physical stress), showed increased social avoidance and reduced hedonic response [153].…”
Section: Combined Impact Of High-fat Diet and Stress Exposure In Rodentsmentioning
confidence: 99%
“…For example, exposure to predator odour threat increased anxiety-related behaviours in HFD-fed rats and reduced brain volume, especially the hippocampal volume, compared to HFD-fed unstressed rats [ 152 ]. In another study, HFD-fed mice subjected to a vicarious social defeat stress, wherein one mouse witnesses the physical defeat of a conspecific from the safety of an adjacent compartment (i.e., uncoupling of emotional and physical stress), showed increased social avoidance and reduced hedonic response [ 153 ].…”
Section: Combined Impact Of High-fat Diet and Stress Exposure In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation